2021
DOI: 10.3390/membranes11020146
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fuel Cell Performance Using Computational Fluid Dynamics

Abstract: A low cost bipolar plate materials with a high fuel cell performance is important for the establishment of Proton Exchange Membrane (PEM ) fuel cells into the competitive world market. In this research, the effect of different bipolar plates material such as Aluminum (Al), Copper (Cu), and Stainless Steel (SS) of a single stack of proton exchange membrane (PEM) fuel cells was investigated both numerically and experimentally. Firstly, a three dimensional (3D) PEM fuel cell model was developed, and simulations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…There are three main layers: a thin electrolyte, a thick anode, and a cathode. The material properties and cell dimensions for the cell components are summarized in Tables 1 and 2, respectively [31][32][33]. The boundary conditions applied to the model are summarized in Table 3.…”
Section: Numerical Modelmentioning
confidence: 99%
“…There are three main layers: a thin electrolyte, a thick anode, and a cathode. The material properties and cell dimensions for the cell components are summarized in Tables 1 and 2, respectively [31][32][33]. The boundary conditions applied to the model are summarized in Table 3.…”
Section: Numerical Modelmentioning
confidence: 99%
“…However, improvements in the technical and economical aspects of the fuel cell are still required for commercialization. Research has been focusing on the optimization of the fuel cell by optimizing the configuration, materials, conformation, and structure of the catalyst layer [5][6][7][8][9]. For instance, several research studies have focused on decreasing the cost of PEMFCs by enhancing the electrolyte conductivity [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…There are lots of studies related to the material and flow field design of HT-PEMFCs. The performance of fuel cells with different bipolar plate materials (aluminum, copper, and stainless steel) was studied numerically and experimentally by Wilberforce et al [8]. It was reported that the fuel cell with the aluminum bipolar plate provides the best performance among the three different materials.…”
Section: Introductionmentioning
confidence: 99%